Identification of Group B Streptococcus Serotypes and Genotypes in Late Pregnant Women and Neonates That Are Associated With Neonatal Early-Onset Infection in a South China Population - Yao, Zhu; Jiayin, Wu; Xinyi, Zheng; Ling, Chen; Mingyuan, He; Simin, Ma; Yayin, Lin; Xinzhu, Lin; Chao, Chen (Frontiers in Pediatrics, 2020)
Background: Group B streptococcus (GBS) colonized in late pregnancies has been associated with neonatal early-onset GBS disease (GBS-EOD) in China. Objective: This study investigated if GBS serotype and genotype in late pregnancy is associated with GBS-EOD, providing a reference for GBS-EOD prevention and treatment. Methods: A total of 298 pregnant women with GBS colonization during their late pregnancy and 32 invasive GBS-EOD cases were included in this study for GBS serotyping and genotyping using commercial kits and DNA sequencing. Results: We identified 266 GBS strains in mothers without newborns who had GBS-EOD. Serotype III [54.9% (146/266)] was the most common serotype, followed by Ib [17.3% (46/266)] and V [10.1% (27/266)]. ST19 was the most prevalent genotype [19.9% (53/266)], followed by ST862 [9.4% (25/266)] and ST12 [7.9% (21/266)]. We found that the 32 mothers and their neonates with GBS-EOD had the same GBS strains.In 32 cases of GBS-EOD, the top three serotypes were III, Ia, and Ib, while the top three genotypes were ST17, ST23, and ST19. ST17 was the dominant genotype of serotype III, which was the most common prevalent in GBS-EOD [72.2% (13/18)], and ST23 was the dominant genotype of serotype Ia, the second most prevalent in GBS-EOD [87.5% (6/8)]. There were statistically significant differences in serotypes(p = 0.046) and genotypes (p = 0.000)distribution between the 266 pregnant women without GBS-EOD neonates and 32 cases of GBS-EOD. Conclusion: This study revealed a statistically significant associations of GBS serotype Ia, and ST17 and ST23 between GBS colonization in women during late pregnancy and in neonatal GBS-EOD.The GBS ST23 of serotype Ia and ST17 of serotype III possessed a strong pathogenicity.